Evaluation of antimicrobial and antiproliferative activities of Actinobacteria isolated from the saline lagoons of northwestern Peru - Clavo R.F. (2021)
Extreme environments Morrope and Bayovar Salt lagoons, several ecosystems and microhabitats remain unexplored, and little is known about the diversity of Actinobacteria. We suggest that the endemic bacteria present in this extreme environment is a source of active molecules with anticancer, antimicrobial, and antiparasitic properties. Using phenotypic and genotypic characterization techniques, including 16S rRNA sequencing, we identified these bacteria as members of the genera Streptomyces, Pseudonocardia, Staphylococcus, Bacillus, and Pseudomonas. Actinobacteria strains were found predominantly. Phylogenetic analysis revealed 13 Actinobacteria clusters of Streptomyces, the main genus. Three Streptomycetes, strains MW562814, MW562805, and MW562807 showed antiproliferative activities against three tumor cell lines: U251 glioma, MCF7 breast, and NCI-H460 lung (non-small cell type); and antibacterial activity against Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 10536, and the multidrug resistant Acinetobacter baumannii AC-972. The antiproliferative activities (measured as total growth inhibition [TGI]) of Streptomyces sp. MW562807 were 0.57 μg/mL, for 0.61 μg/mL, and 0.80 μg/mL for glioma, lung non-small cell type, and breast cancer cell lines, respectively; the methanolic fraction of the crude extract showed a better antiproliferative activity and could inhibit the growth of (U251 (TGI = 38.3 μg/mL), OVCAR-03 (TGI = 62.1 μg/mL), and K562 (TGI = 81.5 μg/mL)) of nine tumor cells types and one nontumor cell type. Extreme enviroments, such as the Morrope and Bayovar Salt saloons are promising sources of new bacteria, whose compounds may be useful for treating various infectious diseases or even some types of cancer. © 2021 Flores Clavo et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.